2012
DOI: 10.1371/journal.pone.0050202
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Cognitive Behavioral Therapy for Depression in Patients Receiving Disability Benefits: A Systematic Review and Individual Patient Data Meta-Analysis

Abstract: ObjectivesTo systematically summarize the randomized trial evidence regarding the relative effectiveness of cognitive behavioural therapy (CBT) in patients with depression in receipt of disability benefits in comparison to those not receiving disability benefits.Data SourcesAll relevant RCTs from a database of randomized controlled and comparative studies examining the effects of psychotherapy for adult depression (http://www.evidencebasedpsychotherapies.org), electronic databases (MEDLINE, EMBASE, PSYCINFO, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…We recently completed a systematic review in which none of 92 randomized controlled trials (RCTs) that explored the effect of CBT on depression reported whether enrolled patients were receiving disability benefits. We successfully contacted 56 trialists and identified 3 trials that captured information on disability benefit status [18]. Our analyses consisting of 2 trials (including 34 patients on disability benefits) did not find a significant difference in depression between patients receiving disability benefits versus those not receiving disability benefits.…”
Section: Introductionmentioning
confidence: 99%
“…We recently completed a systematic review in which none of 92 randomized controlled trials (RCTs) that explored the effect of CBT on depression reported whether enrolled patients were receiving disability benefits. We successfully contacted 56 trialists and identified 3 trials that captured information on disability benefit status [18]. Our analyses consisting of 2 trials (including 34 patients on disability benefits) did not find a significant difference in depression between patients receiving disability benefits versus those not receiving disability benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high level of depression and anxiety in infertile women (44,45), special attention should be paid and appropriate treatments should be provided. CBT effectiveness in reducing anxiety and depression (46,47) has made this technique as an appropriate approach to improve mental health in infertile people and also alleviate their infertility problems.…”
Section: Discussionmentioning
confidence: 99%
“…MDD patients with greater clinical improvement more likely maintain paid employment and report fewer days missed from work [35], and productivity gains following effective depression treatment may far exceed treatment costs [36]. While treatments exist, lack of evidence of an effect of antidepressants alone, enhanced PC, psychological interventions or the combination of these on sickness absence of depressed workers [24] may derive from underuse of optimal treatments [9,15,42]. Thus, improvement of treatment strategies is required [17,27].…”
Section: Discussionmentioning
confidence: 99%